Human skin keratinocytes modified by a Friend-derived retroviral vector: A functional approach (2005)
ABSTRACT: The goal of this study was to test the efficiency and possible functional effects of a Friend Leukemia derived retrovirus vector (FOCH29-NeoR) on cultured human keratinocytes, obtained from skin biopsy samples. The keratinocytes were grown and infected with filtered Friend vector supernatant. After one or two doses of infection, one duplicate of the culture was submitted to selection with G418; the other one was utilized for DNA extraction and PCR modification detection. Transduction efficiency was 46.66 percent and 47.22 percent for one and two doses of infection respectively (range 100 to 15 %). Colony Forming Efficiency (CFE) assays were done with Rodhamine-B staining in nonselected modified cultures and negative controls. There was no difference in CFE (% CFE= 10.74±6.53 negative control vs % CFE= 9.22±5.45 with one dose, and % CFE=10.03±5.74 with two doses of infection). Nevertheless, the cell-cycle analysis done by Propidium Iodade (PI) incorporation and colchicine-arrest assays in nonselected transduced and nontransduced cells show that transduced keratinocytes have a longer time to enter G2. As far as we know, this is the first report of retroviral transduction-induced changes in the cell cycle done on human keratinocytes. This observation is very important because retroviral vectors of genes, such as platelet derived growth factor (PDGF) or vascular endothelial growth factor (VEGF), are expected to facilitate the implementation of these modified cultures for tissue grafting and skin substitute development and potentiate the effectiveness of the grafts.